DESAIN KOMUNIKASI VISUAL DAN BUDAYA LOKAL DI TAMBUN, BEKASI: STUDI LITERATUR TENTANG INTEGRASI TRADISI DAN MODERNITAS - Angga Reza, Yolandita (Fakultas Komputer Dan Desain, 2025)
This research aims to analyze the integration of visual communication design with local culture in Tambun, Bekasi, which is currently faced with the challenges of globalization and modernization. As an area with rapid development, Tambun faces the risk of extinction of local cultural values ​​in various forms of visual communication, which are now dominated by global design trends. Visual communication design has great potential as a medium for preserving and introducing local culture through combining traditional elements, such as batik motifs, traditional symbols and cultural values, into more modern and contemporary designs. This research uses a literature study methodology, reviewing books, scientific journals, articles and case studies from other regions with similar contexts. The research results show that efforts to integrate local culture into visual communication design are starting to appear, but there are big challenges in balancing local elements with the modern aesthetics preferred by the global market. Local designers in Tambun are often faced with a dilemma between maintaining local cultural identity and meeting market demands for minimalist and international designs. Apart from that, there is still a lack of understanding and appreciation of the importance of design based on local culture, both among designers and the general public. This research confirms that the integration of local cultural elements in visual communication design can increase public awareness of the importance of cultural preservation, as well as strengthen local identity amidst globalization.